Decision-making at Life’s End: Sharing the Burden of Responsibility - Quinn, Amanda; Palmer, Amitabha; Nortjé, Nico (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2023)
This case study discusses the challenges of end-of-life decision-making in practice, focusing on the delicate balance between medical paternalism, shared decision-making, and the rights of surrogate decision makers. The family initially struggles to grasp the severity of their loved one’s medical condition but a pivotal moment during the Goals of Care meeting brings sudden clarity. This case explores the appropriateness and implications of the practice of informed non-dissent; and our analysis suggests that it is inappropriate unless there is compelling evidence for decision paralysis. Practical strategies are offered that facilitate compassionate dying care within the constraints of clinical urgency.